PENGARUH PENGETAHUAN TENTANG HIV TERHADAP KESEDIAAN TEST HIV/AIDS DI KAMPUNG SOKANGGO DISTRIK MANDOBO KABUPATEN BOVEN DIGOEL - Martina Mogan (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2022)
Adolescence is a period of rapid growth and development both physically, psychologically or intellectually. Teenagers also tend to dare to take risks for behavior that is done without considering it carefully first. This situation often causes health problems, when teenagers cannot be controlled. Efforts to prevent HIV cases in Indonesia by increasing the knowledge, attitudes and actions of adolescents through youth health services. The aim of the study was to determine the effect of knowledge about HIV on willingness to test for HIV/AIDS in Sokanggo Village, Mandobo District, Boven Digoel Regency.This type of research is descriptive quantitative with a cross sectional study approach. The population is teenagers in Sokanggo Boven Digoel Village and a total sample of 43 people was carried out in January 2020. Data was obtained using a questionnaire and the results of medical record data and analyzed using the chi square test. The results of the study showed that 18 people or 30.2% had less knowledge about HIV in Sokanggo Village, Mandobo District, Boven Digoel Regency, and 25 people or 69.8% had good knowledge. Willingness to test for HIV in adolescents in Sokanggo Village, Mandobo District, Boven Digoel Regency who were not willing to test for HIV were 19 people or 41.9% and respondents who were willing to test for HIV were 24 people or 55.8%. There is an influence of adolescent knowledge on willingness to test for HIV in Sokanggo Village, Mandobo District, Boven Digoel Regency (p-value 0.027 or p <α (0.05).